Semiclassical inverse spectral problem for seismic surface waves in isotropic media: part II. Rayleigh waves. (17th June 2020) - de Hoop, Maarten V; Iantchenko, Alexei; van der Hilst, Robert D; Zhai, Jian
Abstract: We analyze the inverse spectral problem on the half line associated with elastic surface waves. Here, we extend the treatment of Love waves [5 ] to Rayleigh waves. Under certain conditions, and assuming that the Poisson ratio is constant, we establish uniqueness and present a reconstruction scheme for the S-wave speed with multiple wells from the semiclassical spectrum of these waves.